Effect of electron beam irradiation sterilization on biomedical polylactic acid composite filled with Scomberomorus Guttatus-derived hydroxyapatite. (1st November 2019) - Ng, Hon-Meng; Bee, Soo-Tueen; Sin, Lee Tin; Ratnam, Chantara Thevy; Rahmat, A.R.
Abstract: The purpose of this research was to investigate the effects of electron beam irradiation on the properties of polylactic acid (PLA) composites reinforced with bioactive Mackerel-derived hydroxyapatite (MHAp), used for promoting the application in bone regeneration field. The PLA were compounded with 2–10 phr MHAp and were exposed to electron beam irradiation dosages of 10–30 kGy. The results from tensile test and X-ray diffraction analyses indicated that the reinforcing and nucleating effect of MHAp on PLA matrix effectively improved the tensile strength and crystallinity of pristine PLA. Without the addition of MHAp, an increase in irradiation dosages (>10 kGy) gradually decreased the mechanical properties and gel content of unfilled PLA. In contrast, the increasing irradiation dosage up to 20 kGy enhanced the mechanical properties and gel content of MHAp added PLA composites. Such improvement effect is also found to be more significant for samples containing higher loading levels of MHAp that could promote the formation of higher degree of crosslinking network. By this higher crosslinking effect on restricting the polymer chains mobility for extendability and crystallization, the subsequent reduction in the elongation at break and crystallinity of PLA/MHAp samples is thus more prominent for higher loading level of MHAp (≥6 phr) under the increasing irradiation dosages. However, the crystallinity could be increased by further increasing irradiation dose up to 30 kGy due to the occurrence of recrystallization as promoted by the nucleating effect of MHAp particles.